La lunga guerra I Balcani e il Caucaso tra conflitto mondiale e conflitti locali (1912-1923) - Valent, Lucio (Temi di storia, 2020)
Historiography traditionally accepts periodization which considered the First World War as an absolute watershed in the European history as a whole. This text, through a collection of essays by Italian and foreign specialists, seeks to investigate the premises and the results of the First World War in a vast area ranging from the Balkans to the Caucasus normally underrated by historiography, focusing on a series of problems (of ethnic, cultural or political character) which due to their complexity must be faced in an overall framework that takes into account the pre-war period and the first two decades of the twentieth century. The works reveal a very complex and stimulating picture, which leads us to reflect on long-term events and problems that involved all the countries that participated to the regional events, full of consequences for the peoples who lived there.